Рекреаційна місткість зон відпочинку Шацького національного природного парку - Міщенко, Олена Віталіївна; Mishchenko, Olena V. (Тернопільський національний педагогічний університет, 2014)
Запропоновано методику визначення рекреаційної місткості, для національних природних парків, яка передбачає врахування площі досліджуваної залісненої ділянки, показник рекреаційних навантажень, що їй відповідає, стійкість деревостану до цих навантажень, функціональну зону, крутизну схилу. Обґрунтовано доцільність використання коефіцієнта рекреаційно-стаціонарної місткості, який визначається відношенням рекреаційної місткості природного ландшафту та сумарної місткості закладів відпочинку досліджуваної території. Обчислено рекреаційну місткість діючих зон відпочинку Шацького національного природного парку.

In the article the concept “recreation capacity” is defined. Its meaning depends on resistance of natural and anthropogenic landscape. Recreation capacity can be calculated by the acceptable amount of recreational pressure that cannot lead to irreversible changes within the landscape. The methods for calculation of national nature park recreational capacity have been suggested. They take into consideration the environmental differentiated conditions of the park, in particular: functional zone, i.e. a kind of economic activity within the study area, the area of each separate woodland, the index of recreational pressure, which can be determined by growing stock resistance and slope steepness of the relief surface. The application of the coefficient of recreational stationary capacity, which is determined by the ratio of natural landscape recreational capacity to the capacity of national nature park leisure facilities, has been grounded. This approach can be used in planning and designing of recreation areas of national nature parks. The value of recreational capacity for operating recreation Shatskyi National Nature Park: Hriada, Urochysche, Hushevo, Piesochne has been determined. The results of the research show that reacreation area “Piesochne” is characterized by the optimal value of reacreation stationary capacity. The recreation area “Urochysche-Hushevo” is characterized by crucial value. The recreation stationary capacity of recreation area “Hriada” is catastrophic, where the capacity of leisure facilities is 11 times the recreational capacity of the natural landscape. This factor can lead to non-turning landscape complexes changes within the area. The catastrophic situation in recreation area “Hriada” requires an integrated environmental measures, as well as expanding the limits of this area by its removal off the coastal zone of Lake Svitiaz without building new recreation facilities.
Recreation area capacity of shatskyi national nature park
Keywords: національний природний парк; рекреаційна місткість; стійкість природного ландшафту; рекреаційні навантаження; коефіцієнт рекреаційно-стаціонарної місткості; природоохоронні заходи; national nature park; recreation capacity; natural landscape resistance; recreational pressure; coefficient of recreational and stationary capacity; environmental measures